Analysis of local government policy in efforts to realize caries-free Indonesia 2030 in Tasikmalaya City - Kamelia, Emma; Rismayani, Lina; Dewi, Tita Kartika; Setiana, Rena; Robbihi, Hilmiy Ila; Dadang, Abdullah Mubarok (Institute of Computer Science (IOCS), 2024)
Elementary school children are susceptible to dental and oral diseases so they still need special treatment. The prevalence of caries in the elementary school/MI graduate education group exceeds the Indonesian average of 89% and has a caries experience index (DMFT) of 8.2. West Java has a percentage of dental and oral health problems above the national figure of 58%, while data from the Tasikmalaya City Health Office (DKK), in 2017 showed the prevalence of dental caries in elementary school children was 56.2%. The purpose of this study is to examine the policies of the Regional Government in Efforts to Realize Indonesia Free of Caries 2030. In addition, the informants for this study were 3 representatives of UKS teachers in schools fostered by the Health Center and 2 cadres in the Health Center area. Data collection was carried out through Focus Group Discussions (FGD) and in-depth interviews. School Dental Health Efforts (UKGS) with School Health Efforts (UKS) so that time, budget, facilities and infrastructure are inadequate. Conclusion The bureaucratic structure, communication, resources and disposition of Tasikmalaya city in supporting the 2030 caries-free Indonesia program are not sufficient and a Tasikmalaya city regulation is needed to support this.